Study Destination Choice and Career Preferences of International Students at China Pharmaceutical University - Raphael N. Alolga; Said Abasse Kassim; Pierre Dramou (MDPI AG, 2022)
This study had two main thematic aims: first, to determine the factors that influenced the choice of international students at China Pharmaceutical University (CPU) to consider China as a study destination; second, to determine the career preferences of international students upon completion of their various programs of study. As a cross-sectional study, relevant data were collected from undergraduate pharmacy students and postgraduates using a self-administered questionnaire. On the whole, the five most important pull factors that influenced the choice of China as the study destination for the respondents were: (1) quality of education, (2) quality of academic staff, (3) security, (4) desire to obtain a certificate from a foreign country and (5) availability of scholarship opportunities. With respect to the career choices, the top three career preferences of the international students were: (1) to work in the pharmaceutical industry (i.e., pharmaceutical manufacturing companies), (2) to practice clinical pharmacy and (3) to seek employment opportunities outside their countries. This study provides additional details on why China has gradually become a study destination of choice for international students. The career preferences of students could be useful in the design of academic programs that could meet their job aspirations.